Demographic Analysis of the Population in Sofala Province and Access to Health, Mozambique (Research, Society and Development, 2022)
Introduction: The population of Sofala is 2 457 828 inhabitants in an area of 68 081 km², and therefore has a population density of 36.1 inhabitants per km². The continuous population growth of Sofala Province demands more comprehensive access to health services. Objective: The research analyses the demographic situation and access to health services in Sofala Province. Methodology: The study was of the bibliographic review type, the search for the documents was carried out from the post-independence period in the national government websites and reports of the programmes of the Sofala Provincial Directorate of Health. Results: The rapid decline in mortality from 1997 to 2020 did not lead to a change in the age distribution of the population. When comparing the age structure of the population of Sofala province in the census years 1997, 2007, 2017, a very similar distribution to the other provinces is observed. The coverage of the health network in Sofala province is still limited as the theoretical radius of coverage of each primary health unit is 11.01 km, ranging from 17.58 km in Cheringoma to 3.55 km in Beira City. Conclusion: The unequal distribution of human resources, health units and specialized health services for the benefit of the population limits the population's access to services, implying the migration of the rural population to urban areas for access to specialized services.